PROFIL KECEPATAN TENDANGAN SABIT SISWA EKSTRAKURIKULER PENCAK SILAT MTS AL-KAUSAR PEKANBARU - Irfan, Zul; Ramadi, Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This research aims to find out how fast. Sickle Kick forExtracurricular Pencak Silat Students at MTS Al-Kausar Pekanbaru. This research isclassified as a quantitative descriptive research type. The location of this research wascarried out at the MTS AL-Kautsar Kota field, Pekanbaru, Riau Province. Thetechnique used is direct observation of the research object to obtain information aboutproblems occurring in the field. The instrument for this research is the sickle kick speedtest. This test aims to determine the level of sickle kick speed ability of extracurricularpencak silat students at MTS Al - Kausar Pekanbaru. Based on data analysis, a score of25 and above is included in the very good category for two (2) people or 6.67%, with ascore of 20 -24 included in the good category were twenty-three (23) people or 76.6%,for scores 17-19 in the Fair category there were 4 people or 13.3%, for 15-16 in thepoor category one (1) person or 3.33%. And for the very poor category with a score of14 or below, there is none or 0%. Based on the results of this analysis, it can beconcluded that the sickle kick ability possessed by MTS AL-KAUTSAR Pekanbarupencak silat students is in the good category on average with a percentage of 76.6%.Keywords: Pencak Silat Sickle Kick Speed Profile